2017
DOI: 10.1371/journal.pntd.0005863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of signs of trachoma, ocular Chlamydia trachomatis infection and antibodies to Pgp3 in residents of Kiritimati Island, Kiribati

Abstract: ObjectiveIn some Pacific Island countries, such as Solomon Islands and Fiji, active trachoma is common, but ocular Chlamydia trachomatis (Ct) infection and trachomatous trichiasis (TT) are rare. On Tarawa, the most populous Kiribati island, both the active trachoma sign “trachomatous inflammation—follicular” (TF) and TT are present at prevalences warranting intervention. We sought to estimate prevalences of TF, TT, ocular Ct infection, and anti-Ct antibodies on Kiritimati Island, Kiribati, to assess local rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…This tool has been used to assess transmission of both urogenital 7 and ocular 8 infections, including the study on Kiritimati Island, where we showed that there were strong associations between Ct infection, TF and anti-Pgp3 antibody levels. We also observed a rapid increase in Pgp3 seroprevalence throughout childhood years in that population 4 .…”
Section: Introductionsupporting
confidence: 58%
“…This tool has been used to assess transmission of both urogenital 7 and ocular 8 infections, including the study on Kiritimati Island, where we showed that there were strong associations between Ct infection, TF and anti-Pgp3 antibody levels. We also observed a rapid increase in Pgp3 seroprevalence throughout childhood years in that population 4 .…”
Section: Introductionsupporting
confidence: 58%
“…This seroprevalence is within the range of prevalence values previously estimated in post-MDA surveys in Tanzania and Nepal 12,13 . There was also no observed increase in anti-Pgp3 antibody positivity with age in 1–9-year-olds (Supplementary Table 2), in contrast to what is observed in trachoma-endemic settings, whether treatment-naive 16 or after 3 rounds of MDA 15,19 and is in stark contrast to communities with a high prevalence of ocular infection 14 . Focusing on age-specific changes in seropositivity as a measure of cumulative exposure to ocular Ct infection might offset antibody responses from peri-natal infection, as the latter would be expected to be consistent across all ages, or even to decline with increasing age.…”
Section: Discussionmentioning
confidence: 71%
“…Antibodies against Chlamydia trachomatis reflect cumulative exposure to Ct 10 , 11 and it has been suggested that programmes could use some measure of seroprevalence as an alternative indicator of changes in transmission 12 , 13 . Previous work has investigated the use of age-specific seroprevalence for surveillance in the peri- 14 and post-MDA setting 13 , 15 , 16 . Serological techniques for the detection of antibodies against Ct have been used to study the epidemiology of both urogenital and ocular Ct infections 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In Kiritimati, the age‐adjusted prevalence of TF in 1–9‐year‐olds was 28% with age‐ and gender‐adjusted prevalence of TT in those aged ≥15 years was 0.2%. Of the 118 children with TF, 58 (49%) were positive for Ct, compared to 14% of children without TF (26 of 193 swabs) . That is, in Solomon Islands and Fiji, Ct infection does not appear to be the main cause of TF or alternatively TF occurs in the absence of active Ct infection …”
mentioning
confidence: 98%
“…Only in Kiritimati Island of Kiribati, among those with TF, was Ct strongly prevalent on PCR testing . In Kiritimati, the age‐adjusted prevalence of TF in 1–9‐year‐olds was 28% with age‐ and gender‐adjusted prevalence of TT in those aged ≥15 years was 0.2%.…”
mentioning
confidence: 99%